Coaching as a Professional Development Strategy for Adjunct Instructors in a Colombian University - Claudia Gómez Palacio; Deisa Enid Gómez Vargas; Hadaluz Pulgarín Taborda (Universidad Nacional de Colombia, 2019)
This article reports the results of a study in which coaching was used as a professional development strategy with five foreign language adjunct instructors at a public university in Colombia. A questionnaire, coaching sessions, interviews, and both coaches and coachees' reports were the data collection sources. Results showed that adjunct instructors consider coaching a useful professional development strategy that should be offered to all foreign language instructors. In addition, trust and genuine interest were considered determinant when administrators implement this professional development strategy, and self-leadership was crucial when foreign language instructors make decisions regarding their own professional development.